Pneumoperitoneum, Retropneumoperitoneum, Pneumomediastinum, and Diffuse Subcutaneous Emphysema following Diagnostic Colonoscopy - Evangelos Falidas; Georgios Anyfantakis; Konstantinos Vlachos; Christina Goudeli; Boutzouvis Stavros; Constantinos Villias (Case Reports in Surgery)
Colonoscopy is a widely used diagnostic and curative procedure. Extraperitoneal perforation with pneumoretroperitoneum, pneumomediastinum and subcutaneous emphysema combined with intraperitoneal perforation is an extremely rare complication. We report a case of a 78-year-old woman presented to the emergency department with abdominal pain and diffuse abdominal, chest, neck, and facial swelling appeared after a diagnostic colonoscopy. Diagnostic and therapeutic modalities are discussed.